1988
DOI: 10.3109/03093648809078205
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of shock-absorbing insoles during normal walking

Abstract: This paper describes a study of the effectiveness of commercially available shock absorbing insoles when used in four different pairs of shoes during normal walking. The measurement method was based on the use of the Fourier Transform of the axial acceleration of the leg measured by an accelerometer mounted at the ankle. The magnitude of shock was measured by the “Shock Factor” which has been defined as the rms acceleration between 50 Hz and 150 Hz expressed as a proportion of that between 10 Hz and 150 Hz. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Plantar pressures between 2.8 and 3.6 kg/cm 2 have been utilized in prior studies of insole materials. 1,6,10,11,16 Percent compression was determined by measuring the thicknesses of the samples before and after heating with a fine caliper. The percentage of compression required to reach maximal load was compared for the native and heated individual materials and combinations.…”
Section: Testing Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Plantar pressures between 2.8 and 3.6 kg/cm 2 have been utilized in prior studies of insole materials. 1,6,10,11,16 Percent compression was determined by measuring the thicknesses of the samples before and after heating with a fine caliper. The percentage of compression required to reach maximal load was compared for the native and heated individual materials and combinations.…”
Section: Testing Protocolmentioning
confidence: 99%
“…Multiple authors have noted that in the current clinical climate the science of insole design and insole function appears to be somewhat obscured at times by unproven assumptions for their widespread prescription, especially in sports and other common conditions of the foot. 2,9,11,19 The clinical use of insoles is indeed considered fundamental to the treatment of patients with diabetes and other peripheral neuropathies with a risk for, or a history of, plantar ulcerations. 1,2,6,7,15 The purpose of insoles is to reduce force transmission to the plantar foot and lower limb and to protect the foot and reduce the occurrence or recurrence of plantar ulcers in the diabetic populations.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of orthoses in terms of either static [25][26][27] or dynamic [28][29][30] kinetic parameters has been Mean Stride Without Mean Cadence Without Fig. 3 Change in cadence, with/without studied and shows reductions in pressure and ground reaction forces in non RA samples.…”
Section: Effect Of the Orthosesmentioning
confidence: 99%
“…3 Change in cadence, with/without studied and shows reductions in pressure and ground reaction forces in non RA samples. The effectiveness of different types of materials in normal subjects 26,[28][29][30] has also been examined. No studies on EVA orthoses alone have been published, nor do any of the published comparative works include EVA.…”
Section: Effect Of the Orthosesmentioning
confidence: 99%
“…Mizrahi and Susak (1982) found that at impact with one straight leg, after fall from 50 mm, there only remains a maximum acceleration of 46ms-2 at the level of the greater trochanter. Johnson (1988) investigated the influence of shoe insoles on peak acceleration absorption. He defines a shock factor as the integral of the amplitude spectrum from 50 to 150Hz divided by the integral from 10 to 150Hz.…”
Section: Introductionmentioning
confidence: 99%